A novel extracellular matrix-based leukemia model supports leukemia cells with stem cell-like characteristics. (September 2018) - Li, Dandan; Lin, Tara L.; Lipe, Brea; Hopkins, Richard A.; Shinogle, Heather; Aljitawi, Omar S.
Graphical abstract: Highlights: Decellularized Wharton's jelly matrix (DWJM) can be used to culture leukemia. Leukemia cells cultured in DWJM demonstrate increased ALDH expression. Leukemia cells cultured in DWJM demonstrate increased N -cadherin expression. Leukemia cells cultured in DWJM demonstrate increased drug resistance. DWJM could serve as an ECM-based model to study AML stem cell-like behavior. Abstract: Acute myeloid leukemia (AML) relapse results from the survival of chemotherapy-resistant and quiescent leukemia stem cells (LSC). These LSCs reside in the bone marrow microenvironment, comprised of other cells and extracellular matrix (ECM), which facilitates LSC quiescence through expression of cell adhesion molecules. We used decellularized Wharton's jelly matrix (DWJM), the gelatinous material in the umbilical cord, as a scaffolding material to culture leukemia cells, because it contains many components of the bone marrow extracellular matrix, including collagen, fibronectin, lumican, and hyaluronic acid (HA). Leukemia cells cultured in DWJM demonstrated decreased proliferation without undergoing significant differentiation. After culture in DWJM, these cells also exhibited changes in morphology, acquiring a spindle-shaped appearance, and an increase in the ALDH + cell population. When treated with a high-dose of doxorubicin, leukemia cells in DWJM demonstrated less apoptosis compared with cells in suspension. Serial colony forming unit (CFU) assays indicated that leukemia cells cultured in DWJM showed increased colony-forming ability after both primary and secondary plating. Leukemia cell culture in DWJM was associated with increased N-cadherin expression by flow cytometry. Our data suggest that DWJM could serve as an ECM-based model to study AML stem cell-like cell behavior and chemotherapy sensitivity.